Proceedings Fifth Annual Structure in Complexity Theory Conference
DOI: 10.1109/sct.1990.113964
|View full text |Cite
|
Sign up to set email alerts
|

A very hard log space counting class

Abstract: We consider the logarithmic space counting classes #L, opt-L, and span-L, which are defined analogously to their polynomial time counterparts. We obtain complete functions for these three classes in terms of graphs and finite automata. We show that #L and opt-L are both contained in NC', but that, surprisingly, span-L seems to be a much harder counting class than #L and opt-L. We deinonst,rate that span-Lfunctions can be computed in polynomial time if and onlyif P = NP = PH = P(#P), i.e. iff the class P(#P) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
3

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(83 citation statements)
references
References 37 publications
0
80
0
3
Order By: Relevance
“…nondeterministic logspace Turing machines), we obtain the class #PSPACE [18] (resp. #L [1]). Note that for a mapping f ∈ #PSPACE, the number f (x) may grow doubly exponential in |x|, whereas for f ∈ #P, the number f (x) is bounded singly exponential in |x|.…”
Section: Preliminariesmentioning
confidence: 99%
“…nondeterministic logspace Turing machines), we obtain the class #PSPACE [18] (resp. #L [1]). Note that for a mapping f ∈ #PSPACE, the number f (x) may grow doubly exponential in |x|, whereas for f ∈ #P, the number f (x) is bounded singly exponential in |x|.…”
Section: Preliminariesmentioning
confidence: 99%
“…OptL is the function class defined byÀlvarez and Jenner (in [AJ93]) as the logpsace analog of Krentel's OptP [Kre88]. OptL is the class of functions whose values are the maximum over all the outputs of an NL-transducer.Àlvarez and Jenner showed that this class captures the complexity of some natural optimization problems in the logspace setting (eg.…”
Section: Complexity Of Min-uniquenessmentioning
confidence: 99%
“…We will need the following proposition shown in [AJ93]. FL f ∈ OptL, let M be FL machine that makes query to a language L ∈ UL ∩ coUL and computes f .…”
Section: Alvarez and Jenner [Aj93] Definesmentioning
confidence: 99%
“…Certainly the best-known arithmetic class is Valiant's class #P [Val79], consisting of functions that map x to the number of accepting computations of an NP-machine on input x. Recently, the class #L (counting accepting computations of an NL-machine) has also received considerable attention [AJ93,Vin91,Tod92a,MV97].…”
Section: Preliminariesmentioning
confidence: 99%